La protección de los derechos del individuo en el derecho internacional: ¿Es la selectividad compatible con la universalidad?. (2010)
The international protection of human rights has been based on the principle of universality that characterizes this concern of the international law, but the intervention of selectivity criteria has led a discrepancy in the results.Several factors have limited the effective protection: there is no clarity as compared to concepts of enforceability and binding instruments, norm of ius cogens and normative hierarchy; infl uence of the political conjuncture and the international relations between States; States delegate in the different international organizations, the fulfi llment of their obligations; States are selective by political contributors; Regional institutions stimulate the selectivity for having included in their decisions, not legal issues.To face this, international law must restore the original values, on having returned to the origins of the international protection and to the purpose of providing direct access to the individuals before the international institutions that there guarantees both the democracy and the professional impartiality. And the institutional changes that could be justifi ed for the protection sought to transform into a universal reality.